Authenticity of gastronomic events as a function of branding a destination - Čavić, Slobodan; Mandarić, Marija (Hotel and Tourism Management, 2021)
The promotion of authentic food and beverages in Vojvodina is most commonly carried out in gastronomic events. Vojvodina is rich in gastronomic products coming from the households of different nations that inhabit its territory. Gastronomic events with their authenticity can contribute to the creation of the destination brand. The aim of the present study is to explore the authenticity of gastronomic events, which could contribute to a better promotion of Vojvodina and the creation of a recognizable brand of this tourist destination. The research was conducted through the method of survey, using a questionnaire on a sample of 150 respondents. Using statistical methods of binary logistic regression, Chi – square and Fisher‘s test, the analysis was performed and the results were presented. The findings of the research indicate that the authenticity of gastronomic events is recognized by the tourists; however, this should be better utilized in destination branding, as this feature could be the key in attracting tourists.